PHAGOCYTOSIS ACTIVITY OF BINAHONG (Anredera cordifolia (Tenore.) Steenis) FROM SECANG, MAGELANG, CENTRAL JAVA, INDONESIA - Perdana Priya Haresmita; Dika Sotya Sakti; Nunung Yuniarti; Subagus Wahyuono (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2019)
The use of medicinal plants is increasing due to the search for alternative resources to treat diseases such as hypertensions and infection. Along with the development in science, preventive action should take place to prevent our body from suffering from these diseases. This can be done by increasing the human immune status with immunomodulatory agents. Binahong empirically have benefits for wound healing. The purpose of this research was to investigate the immunomodulatory effect of ethanolic extract of binahong leaves. The non-specific modulatory effects of the ethanolic extracts of binahong leaves on the immune systems were measured based on phagocytosis index and phagocytosis capacity. Tests were conducted on strain Balb/C male mice at the age of 6-8 weeks. Mice were administered orally with the extract of binahong leaves (doses of 25, 50, 75 mg/kgBW) for 14 days. The test results with the index parameters and macrophages phagocytosis capacity at doses of 50 and 75 mg/kgBW did not significantly increased when compared with the controls. From these results, we concluded that the ethanolic extract of binahong leaves with a dose of 25, 50 and 75 mg/kgBW cannot significantly the activity of macrophages by phagocytosis index parameters and phagocytosis capacity significantly.